Reducing Health Care Burden of Emergency General Surgery with a 24-Hour Dedicated Emergency General Surgery Service. Issue 5 (May 2022) - Roy, J. David; Hardy, W. Johnson; Roberts, Morgan E.; Stahl, Joseph E.; Butts, C. Caleb; Simmons, Jon D.; Barber, William H.
Background: Emergency general surgery (EGS) diagnoses account for 11% of surgical admissions and 50% of surgical mortality. In this population, 7 specific operations are associated with 80.3% of deaths, 78.9% of complications, and 80.2% of hospital costs. In 2016, our institution established a comprehensive in-house EGS service. Herein, we hypothesize that formation of a dedicated EGS service is associated with a significant reduction in morbidity for patients undergoing the most common EGS procedures. Methods: All patients undergoing one of the most common EGS procedures within 2 days of admission were identified from 1/1/2013 to 5/9/2019 via a retrospective chart review. Patients were cohorted as pre- and post-EGS implementation. The primary outcome measure was the overall complication rate. Secondary endpoints included mortality, individual complication rate, time to operation, overnight operation, and length of stay. Finally, both cohorts were benchmarked to national outcomes. Results: 718 patients met inclusion criteria (pre-EGS = 409 and post-EGS = 309). Overall complication rate decreased significantly (19.8% vs 13.9%, P = .0387) and overnight operations increased significantly in the post-EGS group (7.8%-16.5%, P = .0003). Pre-EGS complications were higher than national data in all but 1 procedure group, whereas post-EGS complications rates were lower in all but 2 categories. Discussion: Implementation of a dedicated EGS service line was associated with a significant decrease in complication rate among the most complication-prone EGS procedures. Number of operations within 24 hours did not increase significantly; however, overnight operations did increase. Our results indicate that establishing a service-specific EGS line is reasonable and beneficial.